Culture Shock pada Mahasiswa Program Pertukaran Mahasiswa Merdeka (PMM) di Universitas Andalas, Kota Padang, Sumatera Barat - Adiprawira, Hardy; Abidin, Zainal; Ramdhani, Muhammad (Peneliti.net, 2023)
The phenomenon of culture shock affects the smooth running of the activities of students participating in the Free Student Exchange (PMM) program. Students must understand the differences, create effective communication, and understand the various differences during the program. The purpose of this research is to find out the stages of culture shock experienced by students and communication activities that occur in students. Sources of data obtained through words and actions, written sources and photographs. This study took five students as subjects who took the Independent Student Exchange Program (PMM) at Andalas University, Padang City, West Sumatra. This study uses communication accommodation, and uses a descriptive qualitative approach. Data collection techniques in this study were in-depth interviews. The results of this study indicate that students experience stages of culture shock consisting of: a) Optimistic Phase, b) Cultural Problems, c) Recovery Phase, d) Adjustment Phase. The impact of culture shock shown to students led to an act of communication accommodation being applied by students of the Free Student Exchange (PMM) program at Andalas University.